Contextualising institutional complementarity. How long‐term unemployment depends on employment protection legislation, active labour market policies and the economic climate. (21st December 2017) - Benda, Luc; Koster, Ferry; van der Veen, Romke
Abstract : This study investigated if and how active labour market policies (ALMPs) and employment protection interact with each other in light of long‐term unemployment reduction. We argue that how well the interaction between both labour market institutions reduces long‐term unemployment depends on the level of economic growth. To improve analytical clarity, two types of ALMPs were differentiated, namely training and employment programmes. Using data on 20 European countries over 16 years, our results suggest that employment protection moderates the relationship between employment programmes and long‐term unemployment. The combination of high spending on employment programmes and less strict employment protection is associated with less long‐term unemployment. This moderation effect is stronger during an economic downturn. A moderation effect from employment protection on the relationship between training programmes and long‐term unemployment was not found, even when the economic climate was taken into account as a contextual factor.